If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.24 = log(x) Multiply glo * x 0.24 = glox Solving 0.24 = glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1glox' to each side of the equation. 0.24 + -1glox = glox + -1glox Combine like terms: glox + -1glox = 0 0.24 + -1glox = 0 Add '-0.24' to each side of the equation. 0.24 + -0.24 + -1glox = 0 + -0.24 Combine like terms: 0.24 + -0.24 = 0.00 0.00 + -1glox = 0 + -0.24 -1glox = 0 + -0.24 Combine like terms: 0 + -0.24 = -0.24 -1glox = -0.24 Divide each side by '-1lox'. g = 0.24l-1o-1x-1 Simplifying g = 0.24l-1o-1x-1
| 4-(x-5)=3(x-11) | | [5x]=10 | | 18-2x=x+19 | | q-1.53=7.04 | | 4.33b=495 | | r+1=7.85 | | 4=-8n | | 13x-3=5x-6 | | 6(x-9)=-30 | | 4.33=495 | | 6+-7=8 | | 16x-3=7x+6 | | 4(36+9y)=-72 | | -7/83/4 | | 4r-6-3=4r-9 | | a(z+5)=32 | | 4x-13=3x-1 | | d−8/−2=12 | | 4(x+6)=3x+4 | | c+3=3(11-3c) | | 6.1=u-3.3 | | x+5y=4z | | 1/2(1/4) | | -9x-6=6x+9 | | 5/4t=10 | | -24=3/4j | | 2.5=g-7 | | (x+5)(x+5)-(x-3)(x+5)= | | 25/4*5/2 | | 15/a=-10 | | 3e+1=e+1 | | 2x+3=9x-1+x |